Non‐invasive CT screening for pulmonary arteriovenous malformations in children with confirmed hereditary hemorrhagic telangiectasia: Results from two pediatric centers. Issue 5 (6th February 2017) - Soysal, Nurcan; Eyries, Mélanie; Verlhac, Suzanne; Escabasse, Virginie; Remus, Natascha; Tamalet, Aline; Rioux, Jean‐Yves; Franchi‐Abella, Stéphanie; Vasile, Manuela; Robert, Sarah; Delestrain, Céline; Hau, Isabelle; et al.
Summary: Background: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant genetic disorder that is caused by mutations in mainly two genes, that is ENG, encoding endoglin (HHT1), or ACVRL1, encoding activin receptor‐like kinase 1 (ALK‐1/HHT2). HHT is characterized by recurrent epistaxis, mucocutaneous telangiectasia, and vascular visceral dysplasia responsible for visceral arteriovenous malformations (AVM). Aim: to report the experience of two university hospitals (Trousseau, Paris, and CHIC, Creteil) with screening children for HHT and pulmonary AVM (PAVM) using high resolution computed tomography (HRCT). Methods: parents with confirmed HHT were offered to have their children screened for the mutation identified in their family, and informed consent was obtained. Children carrying the same mutation as their parents underwent HRCT of the chest without contrast. Results: between 2008 and 2015, 99 children were screened for HHT mutations. Mutations were identified in 59 patients, that is 24 HHT1 and 35 HHT2. Radiologic and clinical screening was possible in 52 patients (21 HHT‐1 and 31 HHT‐2). Among those, PAVM was identified in 13 patients (25%; n = 8 HHT1; n = 5 HHT2), and four of them required embolization therapy. Conclusion: This study highlights the usefulness of genetic screening in children with known HHT family. It also suggests that a non‐invasive protocol such as HRTC is an efficient approach to detect non‐symptomatic lesions that are present early on in children carrying the ENG (HHT1), but also the ACVRL1 mutations (HHT2).Pediatr Pulmonol. 2017;52:642–649. © 2017 Wiley Periodicals, Inc.